3D-printed high-density polyethylene scaffolds with bioactive and antibacterial layer-by-layer modification for auricle reconstruction. (December 2022) - Yin, Junfeiyang; Zhong, Jing; Wang, Jiejie; Wang, Yilin; Li, Ting; Wang, Ling; Yang, Yang; Zhen, Zhifang; Li, Yanbing; Zhang, Hongwu; Zhong, Shizhen; Wu, Yaobin; et al.
Abstract: High-density polyethylene (HDPE) is a promising material for the development of scaffold implants for auricle reconstruction. However, preparing a personalized HDPE auricle implant with favorable bioactive and antibacterial functions to promote skin tissue ingrowth is challenging. Herein, we present 3D-printed HDPE auricle scaffolds with satisfactory pore size and connectivity. The layer-by-layer (LBL) approach was applied to achieve the improved bioactive and antibacterial properties of these 3D printed scaffolds. The HDPE auricle scaffolds were fabricated using an extrusion 3D printing approach, and the individualized macrostructure and porous microstructure were both adjusted by the 3D printing parameters. The polydopamine (pDA) coating method was used to construct a multilayer ε-polylysine (EPL) and fibrin (FIB) modification on the surface of the 3D HDPE scaffold via the LBL self-assembly approach, which provides the bioactive and antibacterial properties. The results of the in vivo experiments using an animal model showed that LBL-coated HDPE auricular scaffolds were able to significantly enhance skin tissue ingrowth and ameliorate the inflammatory response caused by local stress. The results of this study suggest that the combination of the 3D printing technique and surface modification provides a promising strategy for developing personalized implants with biofunctional coatings, which show great potential as a scaffold implant for auricle reconstruction applications. Graphical abstract: Image 1 Highlights: 3D-printed HDPE auricle scaffolds with suitable pore size and connectivity developed. The layer-by-layer (LBL) approach improved bioactive and antibacterial properties. The LBL-coated HDPE auricular scaffolds facilitated skin tissue ingrowth in vitro . The combination of 3D printing and surface modification is a promising strategy.